2022
DOI: 10.1111/idh.12596
|View full text |Cite
|
Sign up to set email alerts
|

Musculoskeletal disorders related to dental hygienist profession

Abstract: Objectives: Musculoskeletal disorders (MSDs) are occupational illnesses concerned with different classes of professionals; dental hygienists are among those. The aim of this trial is to evaluate MSDs prevalence and significance of the symptoms in a sample of dental hygienists. Materials and Methods:A 20-question questionnaire was administered to a sample of dental hygienists, via social networks. The variables taken into consideration were personal data, hours of sport, working habits, years of professional ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 30 publications
(68 reference statements)
2
11
0
Order By: Relevance
“…This was a cross-sectional survey based on a questionnaire. Few data on occupational hazards were available in developing countries [ 5 , 6 , 8 , 9 , 13 – 17 ], and to the best of our knowledge, this was the first study conducted in Yemen. The present study was conducted among dental students, interns, general practitioners, and specialists in 3 facilities of dentistry.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was a cross-sectional survey based on a questionnaire. Few data on occupational hazards were available in developing countries [ 5 , 6 , 8 , 9 , 13 – 17 ], and to the best of our knowledge, this was the first study conducted in Yemen. The present study was conducted among dental students, interns, general practitioners, and specialists in 3 facilities of dentistry.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were identified from a different study, in which 60% of participants reported having MSD. A recent study by Saccucci et al in Italy showed the highest rate of MSD at 91% [ 17 ]. A study from Queensland, Australia, found that younger and less experienced dentists were more likely to report MSDs of the neck, upper back, and shoulders.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations